Melanoma maligno de la mucosa oral. Reporte de un caso (2007)
ABSTRACT: Oral melanomas are rare tumors corresponding to 0.5% of all the oral malignancies. The hard palate and gingiva are more frequently affected. At the moment of diagnosis they are generally in an advanced stage. We describe a case of a 70 years old male with nodular and pigmented lesion in hard palate and other macular pigmented lesions, besides a 2cm cervical nodule. The histo-pathological study showed an extensive infiltration by moderately pleomorphic spindle and epitheliod tumoral cells with melanin pigment in the cytoplasm. Immune-histo-chemical staining was positive to S-100 and HMB-45. Cytology by aspiration of the cervical node was carried out with a fine needle, showing cells with wide cytoplasm and presence of melanin pigment and pleomorphic nuclei. The differential diagnosis includes benign and malign vascular tumors, tumors and cysts of salivary glands, and benign pigmented lesions of the mucosa.